Pectin-Based Active and Smart Film Packaging: A Comprehensive Review of Recent Advancements in Antimicrobial, Antioxidant, and Smart Colorimetric Systems for Enhanced Food Preservation - Nurul Saadah Said; Won Young Lee (Molecules)
This review provides a comprehensive overview of recent advancements in biodegradable active and smart packaging utilizing pectin from various origins for food applications. It critically examines the challenges and limitations associated with these developments, initially focusing on the structural influences of pectin on the properties of packaging films. Methods such as spray drying, casting, and extrusion are detailed for manufacturing pectin films, highlighting their impact on film characteristics. In discussing active pectin films, the review emphasizes the effectiveness of incorporating essential oils, plant extracts, and nanoparticles to enhance mechanical strength, moisture barrier properties, and resistance to oxidation and microbial growth. Smart biodegradable packaging is a significant research area, particularly in monitoring food freshness. The integration of natural colorants such as anthocyanins, betacyanins, and curcumin into these systems is discussed for their ability to detect spoilage in meat and seafood products. The review details the specific mechanisms through which these colorants interact with food components and environmental factors to provide visible freshness indicators for consumers. It underscores the potential of these technologies to fulfill sustainability goals by providing eco-friendly substitutes for traditional plastic packaging.